Analisa Kinerja Pelayanan Angkutan Bus Sedang Jurusan Bukit Kencana – Mangkang - Adi, Rudi Yuniarto (MEDIA KOMUNIKASI TEKNIK SIPIL, 2008)
For supporting the activity of society in Semarang, a city with very large area and population spread, so it is required transportation facility much. With the different society economy grade condition in fulfillment transportation facility necessity, one of the facilities required is Public transportation. Up to now the necessity of load public transportation in Semarang has been served by some kinds of vehicle with different destination (route). One of destinations which is being developed is public transportation by using medium bus with destination of Bukit Kencana to Mangkang. The purpose of this research is to find out the load factor, frequency, headway, keeping watch (waiting) time, vehicle speed, time range of journey and the vehicle age which operate with destination of Bukit Kencana to Mangkang. Whereas the objective of the research is to evaluate the way in which public transportation using medium bus with destination Bukit Kencana to Mangkang operates. The research method used is field research by collecting data relating with the way in which the service operation including load factor, frequency and headway, keeping watch time, speed, time trip, and the age of vehicle. The result of the survey and the data analysis present that the way in which public transportation using medium bus with destination of Bukit Kencana to Mangkang operation is good enough with the following conditions: Maximum keeping watch time reaches 31 minutes, The sum of served passengers on holiday is 281 persons/day, Vehicle utilization is 181, 67 km/day, Availability on holiday is 64,29 %, Speed on an average is 20,50 – 23,15 km/hour , Time range of journey is 86,25 – 91,11 minutes, Mean of Load factor Bukit Kencana to Mangkang is 62,06 % and Mean of Load factor Mangkang to Bukit Kencana is 63,61 %, Vehicle age on an average is 5 years. Keywords : Performance, services, public transportation, medium bus, Bukit Kencana to MangkangPermalink: http://ejournal.undip.ac.id/index.php/mkts/article/view/3666[How to cite: Adi, R.Y. (2008), Analisa Kinerja Pelayanan Angkutan Bus Sedang Jurusan Bukit Kencana – Mangkang, Jurnal Media Komunikasi Teknik Sipil, Tahun 16, No. 1, pp. 61-78]